(3efXheI aj BOGH GdCcd hGdTQHs - (3EHQGgje Hf MSf GdMfajs; (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf, GHf CHj GdOfjG GdbQTj GdCehj (B( (3ehdGge(B) (3, GdHZOGOj, CHh HcQ,J (B281 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH GdYHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JaVdG Ydi GdCfGe HGdfhGd LedG hHYO aGddg GdcQje GdeMUi LGO HaVd eGdg ef eMUQ s
(3BNQgG (B:s
(3hdjS ef BOGHg Cf jLdSG ebGHdkG dHGH MLQg GdfSGA hhGdOjg hcPG ef Ydeg hChd cd GdeSdejf QMeg JeJ GdefXheI GdaQjOI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs